Szkice z powojennych dziejów Przytoku = Sketches from the post-war history of Przytok - Skobelski, Robert (1968- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study of the post-war history of Przytok and its inhabitants is difficult due to the small number of available archival sources, as well as a significant dispersion of information contained in them. In 1945, the village along with the rest the so-called recovered territories, found itself within the borders of Poland. From the 1970s Przytok should be administratively to the commune Zabór. The village was typically agricultural. Currently, about 600 people live here. The most important monument of the village is the neo-renaissance palace, built in the second half of the nineteenth century.
Keywords: Przytok (pow. zielonogórski) - historia; Polska - historia - od 1944 r.; pałac; Poland; palace